Analisis Teks Qiro’ah dalam Kitab Al Arobiyah Lin Naasiin Jilid 2 dalam Efektifitas Pembelajaran - Nur Halim (LP2M STIT Palapa Nusantara, 2020)
The qiroah text in al'arabiyah lin nasiin is very interesting to analyze because the book was compiled by asatidz native Arabic speakers for Indonesia. The ustadz deliberately compile textbooks as well as compile a guidebook for ustadz (the book lil mu'allim), the asatidz besides as a teacher as well as a person who jumped directly in the field. The author wants to know the extent of the form of qiroah text in the book